Seed maturation and yield of sesame cultivar IAC-China - Lago, Antonio Augusto do; Camargo, Octavio Bento de Almeida; Filho, Angelo Savy; Maeda, Jocely Andreucceti (Pesquisa Agropecuaria Brasileira, 2001)
This work aimed to evaluate the development and the physiological and physical quality of seeds of the sesame (Sesamum indicum L.) cultivar IAC-China during the maturation phase. The research was conducted for two successive crop years, in late wet season plantings on a uniform area of the Instituto Agronômico, at Campinas, State of São Paulo, Brazil. The harvests were made at intervals of three to seven days until 150 days after field emergence in the 1993/1994 crop year, and 144 days in 1994/1995; in each harvest, the following determinations were made: moisture content of fruits and seeds, dry matter of 1,000 seeds, yield per plant, and germination during 18 months under uncontrolled storage conditions. The highest dry matter values, largest yields and lowest seed shattering losses occurred at 132 days after emergence in 1993/1994 crop year and at 116 days in 1994/1995. At these optimum harvest stages the seeds presented moisture contents unsuitable to their preservation; after appropriate drying, they exhibited high germination indices at zero, six, twelve and eighteen months of storage. Data from both crop years indicate that the best harvest period for the sesame cultivar IAC-China is situated between 116 and 132 days after field emergence.
Keywords: Sesamum indicum; germinability; dry matter; harvesting date